COVID-19-related complications and decompression illness share main features. Could the SARS-CoV2-related complications rely on blood foaming? (2020)
A study by Saraiva et al. (2011) demonstrated the presence of Angiotensin II receptors on the erythrocyte membrane. This little-known information should be deemed as crucial as the SARS-CoV-2 relationships with oxygen saturation and the Renine Angiotensin System but it currently remains unexploited. The pulmonary and cardiovascular systems are involved in any typical complications of COVID-19 but numerous other unrelated symptoms may occur. To fill the gap, we shall first emphasize some similarities between the complications of this infectious disease and Decompression Illness (DCI), which involves bubble formation. We theorized that the Angiotensin II clearance by the red blood cells could trigger the release of its oxygen content in the bloodstream. The resulting foam would worsen the widespread endotheliitis, worsen the gas exchange, trigger the coagulation process, the inflammation process and the complement pathway as typically occurs in DCI. At the end, we propose a plausible mechanism.